GIS analysis of urban ground collapse susceptibility: a case study of eastern Hangzhou, China - Zhou, Liling; Zhang, Xiaoyi; Shen, Huizhen; Zhang, Dazheng; Bao, Haijun (Frontiers in Earth Science, 2024)
In cities, the intensity of integrated development, both above and below ground, has been continuously increasing. Unfortunately, associated events such as surface cracking and ground collapse are common, and research into the susceptibility of urban ground collapse (UGC) has consequently, also been increasing. In this study, we calculated the spatial probability distribution of histori-cal UGC events in Hangzhou, China as a case study. To avoid the influence of the subjectivity of expert opinions on the evaluation results, and to distinguish it from the first version of the UGC sensitivity map in 2021, collinearity and correlation analyses based on geo-detector were conducted, and the 11 most representative factors from 22 candidates were identified. Then, a GIS-based susceptibility assessment system was established and applied to eastern Hangzhou, China. The assessment results were divided into three grades. High-susceptibility areas accounted for 6.08% of the total area and were mainly distributed in the central area on both sides of the Qiantang River. Medium-susceptibility areas accounted for 23.92% of the total area and showed an expand-ing trend around the central area. Low- susceptibility areas accounted for 12.42% of the total area and were mainly distributed within the bedrock mountainous areas on the west side. The assessment model take more urban construction activies into consid-eration, which can fits better with the trigger factors of UGC itself, and has good applicability for other cities in Zhejiang Province to assess the susceptibility of UGC events.